Prevalence of Helminthes Infection of Stray Dogs in Ilam Province - Abdi, Jahangir; Asadolahi, Khairolah; Maleki, Mohammad Hosein; Ashrafi Hafez, Asghar (Archives of Advances in Biosciences, 2013)
Stray dogs are considered as an important health problem in societies because they can carry dangerous diseases such as hydatidosis, toxocariasis and coenurus cerebralis to humans and animals. Therefore, the study of helminthes infections in all parts of Iran for evaluation of infection state, and provision of the infection control programs is essential. The aim of this study, was to determine the prevalence of parasitic cestodes in stray dogs around Ilam city. In this study, 65 stray dogs were killed by shooting with the municipality officers and were dissected considering health rules. After laparotomy, internal organs are inspected, and bowels completely collected in separate containers containing 10% formaldehyde. Transferring the samples to the parasitological laboratory, the bowels were cut using forceps, and its contents passed through the sieve, and the worms were separated. Azo carmine & carminic acid staining was used for diagnosis of isolated cestodes. The number of 65 dogs, 54 dogs (83%) had at least one species of cestodes; that 32% (21 dogs) infected by Taenia ovis, 9% (6 dogs) by Echinococcus granulosus, 15.4% (10 dogs) by Taenia hydatigena, 20% (13 dogs) by Taenia multiceps, 18.5 /% (12 dogs) by Dipylidium caninum and 10.8% (7 dogs) by Mesocestoides lineatus. In this study, it was shown that helminthic rate in stray dogs is very high around Ilam. These parasites are important in terms of health and economic aspects. Therefore, it is more essential that we note to parasitic infections, to develop control programs.